Rancang Bangun Game Edumatika Berbasis Android - Bakuh Obed Samekto (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2020)
ABSTARCT Education is basic needs should be owned everyone. Especially started from early childhood now tending to love the game finally make it have forgotten learning and make the son to be more lazy to learn. There have been many children the primary school now using gadgets to play games. Many parents also want their children learning not to be forgotten even though in playing. Based on problems above writer had the idea to making researches that contains about learning about early childhood to grade 1. In this study the use writers research study of of building games with doraemon made and implemented berbais 2d game, which uses Fuzzy Tsukamoto method and Linear Congruential Generator (LCG) method. The application of Fuzzy Tsukamoto method into the game to determine the conditions of NPC (Non Player Character) and Linear Congruential Generator (LCG) method for randomizing the appearance of items. The result of this study of Game Edumatika who having the appearance of a whole an interesting and run well. In the material is designed not just as entertainment but also there are learning. Where is the old man has made his son to forget that by learning, because in this game there are also media with at the end of a game there are learning to early childhood. Where is the old man has made his son to forget that by learning, because in this game there are also media with at the end of a game there are learning to early childhood. Keyword: Game Education, Platformer 2D, Metode Tsukamoto, Linear Congruential Generator (LCG) method.